Upaya Meningkatkan Hasil Belajar Fisika Siswa melalui Model Pembelajaran Direct Instruction di Kelas XI. IPA.4 SMAN 2 Lengayang - Febrizanely Febrizanely (Journal on Education, 2023)
This study aims to uncover information and discuss efforts to improve students' physics learning outcomes through the Direct Instruction Learning Model in Class XI. IPA.4 SMAN 2 Lengayang. This type of research is classroom action research (CAR). This research was conducted at SMAN 2 Lengayang, Pesisir Selatan District. The subjects of this study were 32 students of class XI IPA.4 SMAN 2 Lengayang. This research will be carried out in the odd semester of the 2022/2023 school year. The research procedure consisted of two cycles with two meetings in each cycle. Each cycle consists of four stages of research namely planning, implementation, observation and reflection. Data collection in this study was carried out using field note techniques, student worksheets, written tests, observation and documentation. Data analysis techniques use proportion formulas and data reduction. From this research, it was obtained that Class XI Student Learning Outcomes. IPA.4 SMAN 2 Lengayang with the Direct Instruction Learning Model can be seen from the average student learning outcomes in cycle I, namely: 81.88, students who complete 66% or 21 0rang of 32 students. And in cycle II the number of students who completed 90% or 29 people out of 32 students with an average of 86.88. Based on the result data obtained during learning in this class action research it can be concluded that the results of learning Physics through the Direct Instruction Learning Model in class XI. IPA.4 SMAN 2 Lengayang can improve students' physics learning outcomes by giving gifts.